Hypoxia in Peter the Great Bay - P. P. Tishchenko; V. I. Zvalinsky; T. A. Mikhaylik; P. Ya. Tishchenko (Известия ТИНРО)
Studies on hypoxia in Peter the Great Bay (Japan Sea) are reviewed. Seasonal hypoxia is observed in warm season at the bottom of three areas: Amur Bay, Ussuri Bay, and the southwestern part of Peter the Great Bay occupied by the Far-Eastern Marine Biosphere Reserve (FEMBR). Processes of the hypoxia forming are similar in all these areas. The main reason is the dissolved oxygen consumption by microbial degradation of organic matter within topographic depressions in conditions of limited ventilation because of strong summer stratification. The bottom depressions prevent horizontal water exchange and provide accumulation of organic and inorganic suspension, that is another factor important for development of hypoxia. The Amur Bay is the most subjected to hypoxia, being a semiclosed estuarine basin eutrophed by nutrients input from the Razdolnaya River and waste waters of Vladivostok city. The Ussuri Bay has better water exchange and less eutrophication, therefore there are scarce data about hypoxia in this area. FEMBR area has good water exchange and is only episodically influenced by nutrients discharge from the Tumen River, so hypoxia is observed there occasionally. Another consequence of microbial degradation of organic matter in these areas is acidification: pH decreased in 0.5 unit in the bottom water of the Amur Bay in eight decades from 1932 to 2013. Synchronism between regional and global processes of eutrophication, deoxygenation, and acidification of bottom waters is discussed.